2009
DOI: 10.1007/s00063-009-1032-8
|View full text |Cite
|
Sign up to set email alerts
|

Paradigmenwechsel in der Beurteilung myeloischer und lymphatischer Neoplasien bei beruflicher Benzolexposition (BK-Ziffer 1303)

Abstract: Benzene-caused hematologic neoplasms may be recognized as an occupational disease (OD) according to the German ordinance on ODs. At present, the OD No. 1303 covers heterogeneous diseases and various chemical agents triggering these diseases. The members of the medical advisory board specializing in ODs within the Ministry of Employment and Social Affairs recently proposed excluding "diseases of the blood, the hematopoietic and lymphatic system caused by benzene" from OD No. 1303 and classifying them as a separ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 17 publications
0
1
0
2
Order By: Relevance
“…As all hematopoietic tumors result from altered stem cells, some authors suggested that different types of myeloid and lymphoid tumors, comprising their pre-stages, can be provoked by occupational exposure to benzene [ 59 ]. Benzene and its metabolites cause harmfulness toward hemopoietic stem cells (HSCs), comprising short- and long-lasting injury to HSCs, and determine negative effects on the BM hematopoietic milieu [ 60 ].…”
Section: Introductionmentioning
confidence: 99%
“…As all hematopoietic tumors result from altered stem cells, some authors suggested that different types of myeloid and lymphoid tumors, comprising their pre-stages, can be provoked by occupational exposure to benzene [ 59 ]. Benzene and its metabolites cause harmfulness toward hemopoietic stem cells (HSCs), comprising short- and long-lasting injury to HSCs, and determine negative effects on the BM hematopoietic milieu [ 60 ].…”
Section: Introductionmentioning
confidence: 99%
“…(18) En estudios previos describen que la exposición en dosis superiores a 10 ppm por año, es una cantidad suficiente para desarrollar alguna leucemia, debido a que representa hasta un 50 % de probabilidad de causar trastornos hematológicos, siendo los más comunes la leucemia linfocítica crónica, síndrome mielodisplásico, anemia aplásica, pero excluyendo la leucemia mieloide crónica. (19) Por lo que Hayes et al (20) demostraron que existían mayor riesgo de leucemia mieloide aguda, y otras alteraciones hematológicas tanto benignos como malignos, además de que existía posible riesgo de desarrollar cáncer hematopoyético cuando se encuentran expuestos a niveles por debajo de los ya establecidos (1 ppm). Por otra parte, los despachadores que se encontraban laborando 10 años o más desarrollan linfoma no Hodgkin (RR=4,2), mientras que la exposición continua a 25 ppm o superior se halló el síndrome mielodisplásico y leucemia no linfocítica aguda (RR=7,1).…”
Section: Discussionunclassified
“…Dies ist der Fall bei etwa 10 % der MDS-Patienten [5,6]. Eine berufliche Belastung mit organischen Lösungsmitteln, insbesondere Benzol über einen langen Zeitraum, erhöht ebenfalls das Risiko für die Entwicklung eines MDS [7]. Ggf.…”
Section: Diagnostikunclassified